Adsorption of Indigo Carmine onto Chemically Activated Carbons Derived from the Cameroonian Agricultural Waste Garcinia cola Nut Shells and Desorption Studies - Idris-Hermann Tiotsop Kuete; Raoul Donald Tchuifon Tchuifon; Aurelien Bopda; Christian Sadeu Ngakou; George Ndifor-Angwafor Nche; Solomon Gabche Anagho (Journal of Chemistry)
In the quest for a sustainable environment and clean water resources, the efficacy of activated carbons synthesized from Garcinia cola nut shells impregnated with KOH (CBK1/1) and ZnCl2 (CBZ1/1) for the adsorption of indigo carmine (IC) dye was studied using the batch technique. The prepared activated carbons were characterized using iodine number, elemental analysis, scanning electron microscopy (SEM), FTIR spectroscopy, powder X-ray diffraction (XRD), TGA/DTA, Boehm titration, and pH at point of zero charge. The elemental analysis showed a high percentage of carbon in both activated carbons (ACs). FTIR and Boehm titration analysis indicated the presence of several functional groups on the surfaces of both ACs which could influence the adsorption of IC. The primary adsorption mechanisms involved electrostatic interaction, hydrogen bonds formation, and π−π interactions. Maximum adsorption capacity values obtained using the Fritz–Schlunder III three-parameter model were 19.019 mg·g−1 and 18.299 mg·g−1 for CBK1/1 and CBZ1/1, respectively. The Fritz–Schlunder model exponent mFS of value less than 1 showed that the adsorption of IC by the ACs occurred on heterogeneous surfaces. Positive values of ∆Q obtained by the linear and nonlinear forms of the Temkin model indicate the exothermic character of the adsorption process.